Treatment of unstable slipped capital femoral epiphysis with a modified Dunn’s procedure-a case report - Kaul, Rajiv; Mohan Singh, Chander; Thakur, Kamparsh (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2019)
Slipped Capital Femoral Epiphysis (SCFE) is a relatively common disease of adolescents with drastic consequences in adult life if managed inappropriately. Several surgical techniques are described to reposition the proximal femoral epiphysis and are frequently associated with a high rate of femoral head osteonecrosis. The modified Dunn’s procedure has been shown to be safe and effective in treating unstable SCFE. The incidence of development of osteonecrosis is dramatically reduced by carefully preserving the posterior periosteal sleeve, thereby maintaining the vascularity to the head. We have performed this procedure in a 21-year-old male with bilateral, sequential, unstable SCFEs and achieved a satisfactory functional outcome at the end of one year.